Maternal distress and the development of hypertensive disorders of pregnancy. (17th November 2017) - Garza-Veloz, Idalia; Castruita-De la Rosa, Claudia; Ortiz-Castro, Yolanda; Flores-Morales, Virginia; Castañeda-Lopez, Maria E.; Cardenas-Vargas, Edith; Hernandez-Delgadillo, Gloria P.; Ortega-Cisneros, Vicente; Luevano, Martha; Rodriguez-Sanchez, Iram P.; Trejo-Vazquez, Fabiola; Delgado-Enciso, Ivan; et al.
Abstract: Despite the implementation of programmes to improve maternal health, maternal and foetal mortality rates still remain high. The presence of maternal distress and its association with the development of pregnancy hypertensive disorders is not well established. The aim of this study was to evaluate the association between maternal distress and the development of hypertensive disorders in pregnancy in a prospective cohort of 321 Mexican women. Symptoms of maternal distressing were evaluated at week 20th of gestation using the General Health Questionnaire. The presence of acute somatic symptoms, social dysfunction, anxiety and insomnia increased the odds of developing a pregnancy hypertensive disorder by 5.1–26.4 times in study population ( p values  < .05). Our results support the participation of maternal distress in the development of hypertensive disorders of pregnancy. The implementation of effective programmes prioritising risk factors during pregnancy including the presence of maternal distressing factors is recommended. Impact statement: What is already known on this subject: Changes in the nervous, endocrine, and immune systems have been observed in pregnant women with distress conditions leading to gestational disorders. What do the results of this study add: The presence of acute somatic symptoms, social dysfunction, anxiety and insomnia increased the developing of hypertensive disorders in Mexican population. What are the implications of these findings for clinical practice and/or further research: These findings may contribute to a better understanding of the role of the maternal stress in the development of hypertensive disorders of pregnancy, and in the implementation of effective programmes for clinical practice prioritising risk factors during pregnancy, including the presence of maternal distressing factors.